Electronic design and simulation of low cost ocean tides monitoring instrument using Labcenter Proteus - Hollanda Arief Kusuma; Nadya Oktaviani (Journal of Applied Geospatial Information, 2017)
Sea level is one of ocean properties that needed to be observed. Sea level observation will give information about osean tides and tides datum. As technology became more reliable, people can develop new instrument easily. Recently, open source microcontroller “Arduino” became popular and lot of people using it to develop what we call “low-cost” instrument. But, there are several disadvantages if we build instrument directly. Simulation phase must be done before manufacture instrument. This phase will help to decrease cost and time. In this paper, we will describe the concept, algorithm, and simulation phase in manufacturing Low Cost Ocean Tides Monitoring Instrument.